A Beale–Kato–Majda blow-up criterion for a hydrodynamic system modeling vesicle and fluid interactions. (November 2015) - Zhao, Jihong
Abstract: In this paper, we establish an analog of the Beale–Kato–Majda type criterion for singularities of smooth solutions of a hydrodynamic system modeling vesicle and fluid interactions. The result shows that the maximum norm of the vorticity alone controls the breakdown of smooth solutions.